A nanopore structure photocathode with enhanced light absorption and a construction method thereof
By constructing a two-dimensional periodic dot matrix nanopore array on the GaAs photocathode surface and adsorbing a Cs\O activation layer on the lower surface, the problem of insufficient light absorption performance of GaAs photocathode is solved, and higher light absorption rate and quantum efficiency are achieved .
Patent Information
- Application Number
- CN202111210171.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-10-18
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2041-10-18
AI Technical Summary
The existing GaAs photocathodes have insufficient performance in light absorption, especially in terms of nanopore structure, which lacks effective theoretical analysis and implementation.
By constructing a two-dimensional periodic dot array of nanopore arrays on the surface of the GaAs photocathode and adsorbing a Cs\O activation layer on its lower surface, a nanopore structured photocathode with enhanced light absorption is formed.
This technology reduces the refractive index mutation on the GaAs surface, reduces the light reflectance, improves the light absorption rate, and reduces the electron escape work through the Cs\O activation layer and improves the quantum efficiency, thereby significantly improving the performance of the GaAs photocathode.
Smart Images

Figure CN113972288B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of photoelectric material emission, and specifically relates to a nanopore structure photocathode for enhancing light absorption and a construction method thereof. Background Art
[0002] GaAs photocathodes are widely used in low-light image intensifiers, electron microscopes, and new solar cells due to their high quantum efficiency, concentrated electron energy distribution, and low dark current. Therefore, how to improve the performance of GaAs photocathodes has become a research hotspot. Photocathodes achieve photoelectric conversion by absorbing incident light and stimulating photoelectrons, so the ability to absorb incident light directly affects the performance of GaAs photocathodes.
[0003] In order to further enhance the absorption of light by the GaAs photocathode, some microstructures are usually constructed on the GaAs surface to form a light-trapping structure on the surface, which ultimately causes the light to be reflected multiple times in the surface microstructure, thereby achieving the purpose of enhancing light absorption. With the advancement of technology, the size of the surface microstructure that can be made has been further reduced. When the size of the microstructure is smaller than the wavelength, the surface microstructure can be equivalent to a new layer of medium. Since the new medium is formed by etching GaAs, the equivalent refractive index of the new medium is between the material and vacuum. It can be seen from the Fresnel formula that the alleviation of the refractive index mutation can effectively reduce the reflectivity of the material surface, thereby achieving the effect of enhancing the light absorption of the GaAs photocathode.
[0004] At present, the surface microstructure is mainly nanowire structure. Nanowires have a good effect on enhancing the light absorption of GaAs photocathode, but the enhancement effect of nanoholes is not worse than that of nanowires. Nanoholes have better mechanical robustness than other nanostructures and have great prospects for future development. However, there is still a lack of theoretical analysis on nanopore structure GaAs photocathode. Summary of the invention
[0005] The technical problem solved by the present invention is to provide a nanopore structure GaAs photocathode capable of enhancing light absorption
[0006] The technical solution to realize the present invention is: a nanohole structure photocathode with enhanced light absorption, including a GaAs emission layer, a nanohole array and a Cs\O activation layer, wherein the nanohole array is etched on the upper surface of the GaAs emission layer, the Cs\O activation layer is adsorbed on the lower surface of the GaAs emission layer, and light is incident from above the nanohole array; the nanohole array is a two-dimensional periodic lattice arrangement.
[0007] Preferably, the material of the GaAs emission layer is gallium arsenide, the material is P-type doped, and the doping concentration is 1*10 -19 cm -3, the doping atom is Zn.
[0008] Preferably, the thickness of the GaAs emission layer is 1000 nm.
[0009] Preferably, the material used for the nanohole array is consistent with the GaAs emission layer.
[0010] Preferably, the aperture depth of the nanohole array is in the range of 0-400 nm, the duty cycle is in the range of 0.25-1, and the minimum period is in the range of 0-400 nm.
[0011] The present invention also discloses a method for constructing a nanopore structure photocathode for enhancing light absorption, the specific steps of which are:
[0012] Step 1, prepare the GaAs emission layer, specifically:
[0013] The GaAs material was placed in acetone, methanol and isopropanol for ultrasonic treatment for 5 minutes in turn, and then the surface of the GaAs material was rinsed with deionized water to remove the residual organic solvent, and then the surface was dried with nitrogen; the cleaned GaAs material was placed on a heating table and baked at a temperature of 120° to remove the residual moisture; the treated GaAs material was placed in PECVD to grow a layer of SiO2 on the surface, and the SiO2 surface was bombarded with methane for 45 seconds in ICP;
[0014] Step 2, constructing a nanopore array, specifically:
[0015] Spin-coat a layer of negative resist on the surface of the GaAs emission layer; bake the GaAs emission layer with the negative resist at 90° C. for 90 seconds to solidify the negative resist, perform electron beam exposure, develop, and complete cleaning;
[0016] The GaAs emission layer is placed in an inductively coupled ion machine, and CH4 and CHF3 gases are introduced for etching; the negative resist is removed by O2 bombardment;
[0017] Pass two etching gases, Cl2 and BCl3, to etch; soak the GaAs emitter layer with BOE buffer (HF: NH4F = 1:6), remove the SiO2 mask on the top of the GaAs emitter layer, wash the sample with deionized water, and blow dry with nitrogen;
[0018] Step 3: construct the Cs\O activation layer, specifically:
[0019] Turn on the Cs source to enter the Cs activation stage, and use a computer to collect photocurrent in real time for monitoring. When the photocurrent does not rise within the set time or rises to a peak but cannot drop to the preset ratio, turn off the Cs source immediately. Otherwise, it means that the activation is normal and enters the Cs and O alternating activation process;
[0020] Turn on the O source current. If the photocurrent cannot rise within the specified time, stop the activation immediately. If the photocurrent reaches a new peak after the O source is turned on, turn off the O source and compare the peak value of the photocurrent with the previous peak value of the photocurrent. If the ratio of the two is greater than the preset value, continue to activate Cs and O alternately, otherwise enter the closing stage.
[0021] In the final stage, confirm whether the photocurrent can drop to the preset proportion of the peak value within the specified time. If not, end the activation; otherwise, it means that the activation is normal and turn on the O source. If the photocurrent cannot rise within the specified time after the O source is turned on, it means that the activation is abnormal and the activation should be stopped immediately; if the photocurrent rises after the O source is passed and reaches a new peak value, it means that the activation is normal, turn off the O source, pass the Cs source for a certain period of time and then turn it off, and the activation is over.
[0022] Compared with the prior art, the present invention has the following significant advantages:
[0023] (1) The present invention forms a light trapping structure on the GaAs surface by constructing a surface nanopore structure, thereby increasing the number of light reflections and alleviating the refractive index mutation on the GaAs surface, thereby significantly reducing the light reflectivity.
[0024] (2) The present invention reduces the work function of electron escape and improves quantum efficiency by activating Cs\O on the GaAs surface. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a diagram showing the overall structure of the nanopore structure GaAs photocathode of the present invention.
[0026] Figure 2 It is a schematic diagram of the calculation results of the reflectivity, transmittance, absorptivity and average absorptivity of the present invention as a function of aperture depth.
[0027] Figure 3 It is a schematic diagram of calculation results of the reflectivity, transmittance, absorptivity and average absorptivity of the present invention as the duty cycle changes.
[0028] Figure 4 It is a schematic diagram of the calculation results of the reflectivity, transmittance, absorptivity and average absorptivity of the present invention as a function of the minimum period. DETAILED DESCRIPTION
[0029] A nanohole structure photocathode with enhanced light absorption comprises a GaAs emission layer 2, a nanoarray 1 and a Cs\O activation layer 3, wherein the nanoarray 1 is etched on the upper surface of the GaAs emission layer 2, the Cs\O activation layer 3 is constructed on the lower surface of the GaAs emission layer 2, and light is incident from above the nanohole array 1; the nanohole array 1 is a two-dimensional periodic lattice arrangement.
[0030] In a further embodiment, the material of the GaAs emission layer 2 is gallium arsenide, the material is P-type doped, and the doping concentration is 1*10 -19 cm -3 , the doping atom is Zn.
[0031] In a further embodiment, the thickness of the GaAs emission layer 2 is 1000 nm.
[0032] In a further embodiment, the nanohole array 1 is constructed on the GaAs emission layer 2 , and the material used is consistent with the GaAs emission layer 2 .
[0033] In a further embodiment, the aperture depth of the nanohole array 1 is in the range of 0-400 nm, the duty cycle is in the range of 0.25-1, and the minimum period is in the range of 0-400 nm.
[0034] In a further embodiment, a Cs\O activation layer is constructed on the lower surface of the GaAs emission layer 2.
[0035] The present invention constructs a nanohole array 1 on the upper surface of a GaAs emission layer 2, thereby alleviating the sudden change in refractive index between the material and the vacuum, reducing the light reflectivity, and obtaining a GaAs photocathode with a higher absorption rate. Meanwhile, by adsorbing Cs\O on the lower surface of the GaAs emission layer 2, the work function of electrons is reduced, the quantum efficiency is improved, and the performance of the GaAs photocathode is enhanced. The GaAs photocathode can be widely used in the fields of low-light image intensifiers, electron microscopes, and new solar cells.
[0036] The following is a more detailed description through examples
[0037] Example
[0038] A nanopore structure photocathode with enhanced light absorption, such as Figure 1 As shown, it includes a nanohole array 1, a GaAs emission layer 2 and a Cs\O activation layer 3, and its construction method is:
[0039] Step 1 Preparation of GaAs emitter layer
[0040] Prepare a piece of GaAs material with a length and width of 1 cm and a thickness of 1 μm and place it in acetone, methanol, and isopropanol for ultrasonic treatment for 5 minutes. Then rinse the surface of the GaAs material with deionized water to remove the residual organic solvent, and then dry the surface with nitrogen. Place the cleaned GaAs material on a heating table and bake it at 120° for 10 minutes to remove residual moisture. Finally, place the treated GaAs material in PECVD to grow a layer of SiO2 on the surface. After growing SiO2, bombard the SiO2 surface with ammonia in ICP for 45 seconds.
[0041] Step 2: Construction of nanopore array
[0042] After preparing the GaAs emission layer 2, it is also necessary to spin-coat a layer of ma-N2403 negative photoresist on the surface of the GaAs emission layer 2. The spin coating parameters used are: the first step is to spin-coat at 1500rad / min for 3s, and the second step is to spin-coat at 4000rad / min for 29s. After spin coating, a 300nm thick negative photoresist is attached to the surface of the GaAs emission layer 2. Then the sample with the negative photoresist is baked on a heating table at 90°C for 90s to solidify the negative photoresist. The electron beam exposure system used is the Raith150-TWO electron beam exposure system. First, adjust the focus, numerical aperture and astigmatism of the electron beam, then adjust the exposure area and exposure dose, and finally import the selected pattern into the mask pattern program for exposure. After the exposure is completed, place the sample in the ma-D525 developer for 2 minutes.
[0043] After the development and cleaning are completed, the GaAs emission layer 2 is placed in an inductively coupled ion machine (ICP), and two gases, CH4 and CHF3, are introduced, with flow rates of 20sccm and 36sccm respectively, a chamber pressure of 120mT, an etching power of 800w, and an etching time of 2min40s. After the etching is completed, the negative resist is removed by O2 bombardment, with an O2 flow rate of 0.8sccm, a chamber pressure of 120mT, a power of 800w, and a bombardment time of 2min. After removing the negative resist, an electron microscope is required to check the etching effect.
[0044] Prepare two etching gases, Cl2 and BCl3, with flow rates of 20sccm and 7.0sccm respectively, chamber pressure of 120mT, etching power of 800w, and etching time of 4min. After etching, soak the sample in BOE buffer (HF: NH4F = 1:6) to remove the SiO2 mask on the top of the GaAs emitter layer. Finally, wash the sample with deionized water and blow dry with nitrogen.
[0045] Step 3 Construction of Cs\O activation layer
[0046] First, turn on the Cs source to enter the Cs activation stage, and use a computer to collect photocurrent in real time for monitoring. If the photocurrent does not rise for a long time or rises to a peak but cannot drop to the preset ratio, the Cs source should be turned off immediately, otherwise it means that the activation is normal and the (Cs, O) alternating activation process can be entered.
[0047] Turn on the O source current. If the photocurrent cannot rise within the specified time, stop the activation immediately. If the photocurrent reaches a new peak after the O source is turned on, it means that the activation is normal. At this time, turn off the O source and compare the peak value of the photocurrent with the previous peak value of the photocurrent. If the ratio of the two is greater than the preset value, continue to perform (Cs, O) alternating activation, otherwise enter the closing stage.
[0048] In the final stage, it is first necessary to confirm whether the photocurrent can drop to the preset proportion of the peak value within the specified time. If not, the activation is terminated; otherwise, it means that the activation is normal and the O source is turned on. If the photocurrent cannot rise within the specified time after the O source is turned on, it means that the activation is abnormal and the activation should be stopped immediately; if the photocurrent rises and reaches a new peak after the O source is passed, it means that the activation is normal, turn off the O source, pass the Cs source for a certain period of time and then turn it off, and the activation is over.
[0049] like Figure 2 As shown in (a), the anti-reflection performance of the nanohole array will change according to the different aperture depths. An aperture depth that is too small or too large cannot achieve the best anti-reflection performance. Although the construction of the nanohole array will increase the transmittance of the photocathode to light, the anti-reflection effect of the nanohole array can compensate for this part well. Figure 2 As shown in (d), when the pore depth of the nanopore array is 60 nm, the average absorption rate of the nanopore array is as high as 77.71%, which is 17.25% higher than the average absorption rate without the nanopore array.
[0050] like Figure 3 As shown in (a), the anti-reflection performance of the nanohole array is not only affected by the aperture depth, but also by the duty cycle. When the duty cycle is 0.25 and 0.3, troughs appear at 460nm and 505nm, respectively, and the reflectivity of the nanohole array has minimum values of 0.4% and 1.1%, respectively. Figure 3 As shown in (d), when the duty cycle is 0.3, the average absorption rate is as high as 87.71%, which is 27.25% higher than the average absorption rate without the nanohole array.
[0051] like Figure 4 As shown in (a), after determining the optimal aperture depth and duty cycle, the period of the nanohole array can be changed to obtain the period with the best anti-reflection performance. Figure 4 (d) It can be seen that when the period is 100 nm, the nanohole array has the best effect of enhancing light absorption, with an average absorption rate of 87.71%, which is 27.25% higher than the average absorption rate without the nanohole array.
Claims
1. A nanopore structure photocathode with enhanced light absorption, characterized in that: It includes a GaAs emission layer, a nanohole array and a Cs\O activation layer. The nanohole array is etched on the upper surface of the GaAs emission layer, and the Cs\O activation layer is adsorbed on the lower surface of the GaAs emission layer. Light is incident from above the nanohole array. The nanohole array is a two-dimensional periodic lattice arrangement. The material of the GaAs emission layer is gallium arsenide, which is P-type doped with a doping concentration of 1*10 -19 cm -3 , the doping atom is Zn, the thickness of the GaAs emission layer is 1000nm, the material used for the nanohole array is consistent with the GaAs emission layer, the aperture depth range of the nanohole array is 0-400nm, the duty cycle range is 0.25-1, and the minimum period range is 0-400nm.
2. A method for constructing a nanopore structure photocathode with enhanced light absorption according to claim 1, characterized in that: The specific steps are: Step 1, prepare the GaAs emission layer, specifically: The GaAs material was placed in acetone, methanol and isopropanol for ultrasonic treatment for 5 minutes in turn, and then the surface of the GaAs material was rinsed with deionized water to remove the residual organic solvent, and then the surface was dried with nitrogen; the cleaned GaAs material was placed on a heating table and baked at a temperature of 120° to remove the residual moisture; the treated GaAs material was placed in PECVD to grow a layer of SiO2 on the surface, and the SiO2 surface was bombarded with methane for 45 seconds in ICP; Step 2, constructing a nanopore array, specifically: Spin-coat a layer of negative resist on the surface of the GaAs emission layer; bake the GaAs emission layer with the negative resist at 90° C. for 90 seconds to solidify the negative resist, perform electron beam exposure, develop, and complete cleaning; The GaAs emission layer is placed in an inductively coupled ion machine, and CH4 and CHF3 gases are introduced for etching; the negative resist is removed by O2 bombardment; Pass Cl2 and BCl3 etching gases to etch. Soak the GaAs emitter layer in BOE buffer (HF: NH4F = 1:6), remove the SiO2 mask on the top of the GaAs emitter layer, wash the sample with deionized water, and blow dry with nitrogen. Step 3: construct the Cs\O activation layer, specifically: Turn on the Cs source to enter the Cs activation stage, and use a computer to collect photocurrent in real time for monitoring. When the photocurrent does not rise within the set time or rises to a peak but cannot drop to the preset ratio, turn off the Cs source immediately. Otherwise, it means that the activation is normal and enters the Cs and O alternating activation process; Turn on the O source current. If the photocurrent cannot rise within the specified time, stop the activation immediately. If the photocurrent reaches a new peak after the O source is turned on, turn off the O source and compare the peak value of the photocurrent with the previous peak value of the photocurrent. If the ratio of the two is greater than the preset value, continue to activate Cs and O alternately, otherwise enter the closing stage. In the final stage, confirm whether the photocurrent can drop to the preset proportion of the peak value within the specified time. If not, end the activation; otherwise, it means that the activation is normal and turn on the O source. If the photocurrent cannot rise within the specified time after the O source is turned on, it means that the activation is abnormal and the activation should be stopped immediately; if the photocurrent rises after the O source is passed and reaches a new peak value, it means that the activation is normal, turn off the O source, pass the Cs source for a certain period of time and then turn it off, and the activation is over.
3. The method for constructing a nanopore structure photocathode with enhanced light absorption according to claim 2, characterized in that: In step 2, a layer of ma-N2403 negative resist is spin-coated, and the spin-coating parameters used are: 1500 rad / min for 3 s, and 4000 rad / min for 29 s.
4. The method for constructing a nanopore structure photocathode with enhanced light absorption according to claim 2, characterized in that: In step 2, the flow rates of CH4 and CHF3 gases are 20 sccm and 36 sccm respectively, the chamber pressure is 120 mT, the etching power is 800 W, and the etching time is 2 min 40 s.
5. The method for constructing a nanopore structure photocathode with enhanced light absorption according to claim 2, characterized in that: The two etching gases, Cl2 and BCl3, have flow rates of 20 sccm and 7.0 sccm respectively, the chamber pressure is 120 mT, the etching power is 800 w, and the etching time is 4 min.
Citation Information
Patent Citations
Variable-Al component transmission GaAlAs photocathode with ultrathin GaAs emission layer
CN108649076A
Substrate-active layer composite nano photonics structure alkali metal compound photocathode
CN111477524A